Characterization of Citrusnobilis Peel Methanolic Extract for Antioxidant, Antimicrobial, and Anti-Inflammatory Activity - Anjali Malik; Agnieszka Najda; Aarti Bains; Renata Nurzyńska-Wierdak; Prince Chawla (Molecules, 2021)
Currently, the potential utilization of fruits and vegetable waste as a source of micronutrients and antioxidants has increased. The present study, therefore, aimed to determine the antimicrobial and anti-inflammatory activities of Citrus nobilis peel extract. A modified solvent evaporation technique was employed for peel extract preparation. For effective utilization of the natural product, quantitative analysis of phenolic compounds was carried out using liquid chromatography and mass spectroscopy technique. Phenolic and flavonoids were present in high amounts, while β-carotene and lycopene were present in vestigial amounts. The antimicrobial efficiency of peel extract was evaluated against four bacterial strains including Staphylococcus aureus (MTCC 3160), Klebsiella pneumoniae (MTCC 3384), Pseudomonas aeruginosa (MTCC 2295), and Salmonella typhimurium (MTCC 1254), and one fungal strain Candida albicans (MTCC 183), and zone of inhibition was comparable to the positive control streptomycin and amphotericin B, respectively. The extract of Citrus nobilis peels showed effective anti-inflammatory activity during human red blood cell membrane stabilization (HRBC) and albumin denaturation assay. The extracts also exhibited 2,2-diphenyl-1-picrylhydrazyl (DPPH) scavenging activity ranging from 53.46 to 81.13%. Therefore, the obtained results suggest that Citrus nobilis peel could be used as an excellent source of polyphenols and transformed into value-added products.